إطار مقترح لتفعيل دور معلومات تكاليف الجودة في عملية اتخاذ القرار في المنشآت الصناعية - زيود لطيف; أسعد باسل; ياسين أيام (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث بشكل عام إلى محاولة تحديد اتجاهات التطوير لتوفير المعلومات المالية التي يمكن من خلالها ليس فقط قياس تكاليف الجودة بل محاولة ترشيد هذه التكاليف في إطار السعي إلى تخفيض التكاليف الكلية, ويتم ذلك من خلال تقديم إطار مقترح لتجميع وقياس تكاليف الجودة في المنشآت الصناعية يكون قادراً على توفير المعلومات عن أنشطة الجودة التي يحتاجها متخذ القرار في ظل التطورات الصناعية والتكنولوجية المتجددة, وتتجلى أهمية ذلك في كونه يعزز نشر ثقافة الجودة ومفاهيم تكاليف الأنشطة المترتبة عليها وأهمية تجميعها وتبويبها بغرض استخدامها في عملية اتخاذ القرار, وقد عرضت أركان الإطار المقترح ووضحت منهجية تطبيقه والمساهمات التي من الممكن أن يقدمها للمنشآت الصناعية, كما أكدت التوصيات على ضرورة تحسين الأداء الصناعي وتطوير نماذج قياس والتقرير عن تكاليف الجودة وإجراء البحوث التطبيقية, ونشر ثقافة المفاهيم الحديثة للجودة والتكلفة. This research attempts to identify the development trends to provide the financial information through which we do not only measure the quality costing, but we try to rationalize these costs in an attempt to reduce the total costs. This is done through providing a suggested framework to gather and measure quality costing in industrial institutions. The framework should provide the information about quality activities that the decision maker needs within the evolving technological and industrial developments. Its importance is evident in spreading quality education and the concepts of related activity costing, the importance of gathering and sorting them to be used in decision making process. I have shown the elements of the suggested framework, and put forward the methodology of implementing it, and the contribution that can be offered to the industrial institutions. I asserted the necessity of improving the industrial performance and developing models of measuring and reporting the quality costing and performing the field research and spreading the modern concepts of quality costing.